Evolution of Yangrup Thum (1256-1780 A.D.) - Yonghang, Manu (Kanakai Journal, 2024)
This article examines and analyses the evolution of Yangrup Thum, a small state of eastern Nepal, which was invaded by Gorkha during the unification of Nepal and its identity was completely dominated by Gorkha after the war held in 1780 which kept the Thum completely in the dark more than two centuries about its sociological, political, cultural, and economic aspects. The study explores how the military power of Gorkha and Makawanpur violated human right and introduced crime and injustice with inhumanity to looser states. Only a small amount of research work has been done on the history of Yangrup Thum and is unable to reflect its historical background. Researchers found the great history described by some foreign writers and its effect on Yangrup Thum to reflect the historical condition about its effect to neighbouring countries and the forgetting its name and fame first decade after domination. Even the Thum was formed into five different rural municipalities in Taplejung and Panchthar districts having more than seventy thousand people, who had lack of knowledge about their history, so this article helps them to gain knowledge about their past. The sources available enlighten the preliminary history of Yangrup Thum. The close relationship with neighbouring states like Sikkim, Bhutan, Tibet, Makawanpur, Purniya, and Vijayapur influence the power distribution into neighbouring country however after defeat in war, the well-developed society had gone in completely dominate that the dark age of Yangrup Thum started. The primary and secondary data and facts have been drawn from different sources and reviews made by the critics, and they are interpreted and analysed.